Growth performance and production efficiency of indigenous chickens in different dietary of protein levels and rearing duration - Rizkuna, Akhmat; Fajrih, Nurul; Aldiyanti, Amani; Yusuf, Roosena; Fadillah, Muhammad Rizki (Politeknik Negeri Jember, 2026)
Feed cost represents the largest component of poultry production, making feed efficiency a key determinant of economic sustainability. Indigenous chickens are economically and culturally important but exhibit relatively slow growth and suboptimal feed utilization. This study evaluated the effects of different dietary protein regimens on growth performance of indigenous chickens, focusing on feed conversion ratio (FCR), feed efficiency (FE), and performance index (PI). A total of 168 day-old chicks were reared for 10 weeks in a completely randomized design (four treatments, six replicates). The treatments consisted of: T0 (22% crude protein for 3 weeks followed by 15% for 7 weeks), T1 (18% for 4 weeks followed by 16% for 6 weeks), T2 (18% for 2 weeks, 16% for 4 weeks, and 14% for 4 weeks), and T3 (18% for 3 weeks, 16% for 3 weeks, and 14% for 4 weeks). Dietary protein level significantly affected FCR and FE (P<0.05). T0 produced the lowest FCR (3.35) and highest FE (37.20%), whereas T2 and T3 showed higher FCR values (4.47) and lower FE (25–28%). Results indicate that adequate protein supply during the starter phase is critical to long-term feed efficiency. Diets with balanced protein levels and appropriate energy–protein ratios improve nutrient utilization and overall production performance in indigenous chickens.